EPSP of L. casei BL23 Protected against the Infection Caused by Aeromonas veronii via Enhancement of Immune Response in Zebrafish - Qin, Chubin; Zhang, Zhen; Wang, Yibing; Li, Shuning; Ran, Chao; Hu, Jun; Xie, Yadong; Li, Weifen; Zhou, Zhigang (Frontiers in Microbiology, 2017)
Aquaculture is the fastest-growing food production sector in the world, and it supplies nearly 50% of the global food fish supply. However, disease outbreaks have become a major problem in the fish farming industry. The beneficial contribution of probiotic bacteria to aquatic animals’ health has been widely described, and they have been widely used in aquaculture for disease control and growth promotion. However, the action of probiotic bacterial components and mechanisms underlying protection against pathogens afforded by probiotic bacteria remain poorly understood. In the present study, we pre-colonized zebrafish larvae (before hatching) with 17 potential probiotic bacterial strains and screened for those possessing anti-infective effects against Aeromonas veronii. We found that Lactobacillus casei BL23 significantly increased the survival of zebrafish larvae upon A. veronii infection. Using a germ-free (GF) zebrafish model and gut microbiota transplant experiment, we showed that L. casei BL23 per se has anti-infective effects in zebrafish larvae, which does not involve microbiota. Furthermore, we identified an exopolysaccharide-protein complex (EPSP) extracted from L. casei BL23 cells, which consisted of a 40–45 KD size protein and an exopolysaccharide composed of α-Rha, α-Glc, β-GlcNAc, and β-GalNAc. EPSP significantly increased the survival rate of GF zebrafish at a dose of 10–20 μg/ml after A. veronii infection (P < 0.01). In addition, the EPSP induced a higher expression of TLR1 and TLR2, and modulated the expression profile of pro-inflammatory and anti-inflammatory cytokines in zebrafish liver (ZFL) cells. Our data indicated that the anti-infective effect of EPSP from L. casei BL23 was mediated by enhancement of immune responses in zebrafish, which might involve the TLR1/TLR2 signal pathway.